2011
DOI: 10.1371/journal.pone.0024471
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Human A/H1N1 and A/H3N2 Influenza Virus on Corsica Island: Phylogenetic Analysis and Vaccine Strain Match, 2006–2010

Abstract: BackgroundThe aim of this study was to analyse the genetic patterns of Hemagglutinin (HA) genes of influenza A strains circulating on Corsica Island during the 2006–2009 epidemic seasons and the 2009–2010 pandemic season.MethodsNasopharyngeal samples from 371 patients with influenza-like illness (ILI) were collected by General Practitioners (GPs) of the Sentinelles Network through a randomised selection routine.ResultsPhylogenetic analysis of HA revealed that A/H3N2 strains circulating on Corsica were closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…Alternatively, a D222E substitution was found in 1 of the isolates, A/Yamaguchi/247/2009, which was derived from a fatal infection. This substitution, however, seems to be unrelated to the disease severity of the A(H1N1)pdm09 as previously reported (4,8). Another V132E amino acid mutation in the receptor binding site was found in 2 isolates, a fatal casestrain (i.e., A/Tochigi/2/2010) and a mild case-strain (i.e., A/Yamaguchi/273/2009); however, the precise impact of this mutation is unclear.…”
supporting
confidence: 82%
“…Alternatively, a D222E substitution was found in 1 of the isolates, A/Yamaguchi/247/2009, which was derived from a fatal infection. This substitution, however, seems to be unrelated to the disease severity of the A(H1N1)pdm09 as previously reported (4,8). Another V132E amino acid mutation in the receptor binding site was found in 2 isolates, a fatal casestrain (i.e., A/Tochigi/2/2010) and a mild case-strain (i.e., A/Yamaguchi/273/2009); however, the precise impact of this mutation is unclear.…”
supporting
confidence: 82%
“…24 Corsican laboratoryconfirmed influenza cases were reported by Sentinelles GPs. 22,25 Nasopharyngeal swabs were collected through a randomized selection routine. GPs included the first patient of each week, of any age (Sentinelles protocol) or of a personally assigned age group among 0-4, 5-14, 15-64, and >65 y-old (GROG protocol).…”
mentioning
confidence: 99%
“…Majority of the Lucknow strains contained N402D mutation in the NA coding sequences which represents the loss of the N‐linked glycosylation site in the NA domain [Sobolev et al, ]. Variation in the N‐glycosylation sites at HA and NA domain may potentially alter the antigenic property of the glycoprotein and its function [Falchi et al, ]. Many studies reported the mutations associated with the NA protein (i.e.…”
Section: Discussionmentioning
confidence: 99%